The Global Wellposedness and Scattering of the Generalized Davey-Stewartson Equation (Journal of Partial Differential Equations, 2004)
We discuss the solution of the Cauchy problem of the generalized Davey-Stewartson equation. When the initial value is small enough, we obtain the global wellposedness of the solution and scattering.
Keywords: The generalized Davey-Stewartson equation; the Cauchy problem; scattering